Infrastructure-Integrated Photovoltaic-Thermal (IIPV/T) Systems for Anti-Icing Applications in Highway Bridges: A Sustainable Approach - Valinejadshoubi, Masoud; Bagchi, Ashutosh; Athienitis, Andreas K. (Standards-related Regional Innovation and International Cooperation, 2025)
This paper investigates the potential of a novel, infrastructure-integrated photovoltaic/thermal (IIPV/T) system for winter road maintenance, using the Samuel De Champlain Bridge in Montreal as a case study. Vertically mounted bifacial PVT panels are integrated into the bridge’s side barriers, serving a dual role as wind protection structures and clean energy generators. The captured solar energy is used in real time and stored seasonally to power a hydronic heating system (HHP) for anti-icing the bridge deck.The system is modeled using NREL’s System Advisor Model (SAM) with Typical Meteorological Year (TMY) data for Montreal. Simulations estimate that approximately 45% of winter heat demand can be met directly from IIPV/T generation, while 20% is supplied via seasonal thermal storage, and the remaining 35% is surplus. A comparative energy analysis between the Champlain Bridge and an existing Swedish system is presented. Economic analysis indicates a payback period of 2.1–2.5 years, with additional benefits from grid-connected surplus electricity.This study demonstrates the technical and economic feasibility of using IIPV/T systems for sustainable anti-icing of large-scale infrastructure. Limitations such as structural load effects and detailed pipe heat losses are noted and recommended for future work.